SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN BERBASIS WEBSITE DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) Di SMA NEGERI 6 TANGERANG SELATAN - Tasya Julia Permata (2021)
SHS ( Senior High School ) is one of the further education levels from JHS ( Junior High School ). SMA 6 Negeri Tangerang Selatan is one of the high schools located in Komplek pamulang permai 1, Tangerang Selatan, Banten. SMA 6 Negeri Tangerang Selatan Has 2 Departments, namely Science and Social Sciences. One of the activities of SMA is the selection of majors as a process of placement or distribution in the selection of teaching programs for students which are the main focus of the subject areas taken. The purpose of this study is to create a decision support system in choosing the right department according to the specified criteria. In conducting this study the authors used the Simple Additive Weighting (SAW) method. This method is taken because there is a ranking process that will select the best alternative from a number of alternatives. The results to be achieved in this study are in the form of a recommendation application that can help the school to determine the inclusion of students according to the existing majors with the criteria for the value obtained.